An investigation into a contactless photoplethysmographic mobile application to record heart rate post-exercise: Implications for field testing - Peart Daniel J.; Shaw Matthew P.; Rowley Chris G. (Sciendo, 2015)
Study aim: the aim of this study was to compare the accuracy of a contactless photoplethysmographic mobile application (CPA) to record post-exercise heart rate and estimate maximal aerobic capacity after the Queen's College Step Test. It was hypothesised that the CPA may present a cost effective heart rate measurement tool for educators and practitioners with limited access to specialised laboratory equipment.